Why public health needs GIS: a methodological overview. Issue 1 (2nd January 2020) - Wang, Fahui
ABSTRACT: The short paper provides an overview on how geographic issues have become increasingly relevant to public health research and policy, particularly through the lens of geographic information systems (GIS). It covers six themes with an emphasis on methodological issues. (1) Our health-related behaviour varies across geographic settings, so should public health policy. (2) Facilities (supply) and patients (demand) in a health-care market interact with each other across geopolitical borders, and measures of health-care accessibility need to capture that. (3) Our health outcome is the result of joint effects of individual attributes and neighbourhood characteristics, and an adequate definition of neighbourhood is critical for assessing neighbourhood effect. (4) Disease rates in areas of small population are unreliable, and one effective way to mitigate the problem is to construct a larger, internally homogenous and comparable area unit. (5) Defining a scientific geographic unit for health-care market is critical for researchers, practitioners, and policy makers to evaluate health-care delivery, and GIS enables us to define the unit (e.g. primary care service areas, hospital service areas, and cancer service areas) automatically, efficiently and optimally. (6) Aside from various optimization objectives around 'efficiency', it is as important to plan the location and allocation of health-care resources towards maximum equality in health-care access. Case studies are cited to illustrate each theme.